Research on Risk Culture of Bank A - YU, BING (2019)
This paper explores the topic of risk culture in conjunction with published literature reviews. The purpose of the research was to determine whether the measurement of risk culture within the organization could guide risk management practices. Subsequently, through the literature reading, questionnaire survey and data analysis, the risk culture of the research bank A was studied. The research mainly uses qualitative research methods, but at the same time some quantitative tools are used for auxiliary data analysis. The research found that Bank A's risk cultural flaws were affected by its own risk management model. So the paper puts forward some suggestions for improvement. The contribution of this study is to apply the indicator scoring method to the measurement of bank risk culture in China.